(untitled) (Zaporizhzhia Historical Review, 2021)
The tasks of the article are to analyze the process of recruiting persons to the new cossacks senior officer and its vertical and horizontal mobility. The influence of senior officer on forming of political position and ideology of Free the cossacks in 1917-1923 years and its relationships with a ruling political and military elite has considered. The process of forming of ideology of Free cossacks movement on emigrations and role herein of apex of Free cossacks movement was explored. The relationships of cossack elite with the representatives of other elites groups of Ukrainian emigration has learned. The archived funds, memoirs, materials of periodic press, are the springing base of research 1917-1985 years.